Use of a new aiming compression device and technique for the repair of navicular bone fractures in horses: A cadaveric study - Pudert, Tanja; Fries, Giuletta Felicia; Lotz, Hannah; Röcken, Michael; Cruz, Antonio M.; Justus Liebig University Giessen (My University, 2025)
Objective: To assess the use of a newly developed aiming compression device (ACD) for screw insertion in non-fractured navicular bones (NB) in cadavers. Study design: Cadaveric study. Sample Population: A total of 10 cadaveric front limbs of adult horses. Methods: Placement of a 3.5 mm cortical screw in non-fractured NB under radiographic guidance was performed in 10 cadaver limbs in a standing position. An ACD was used to stabilize the NB and to guide the drilling process. Preparation and surgical time as well as the number of radiographic images were noted. A postoperative scoring system was used to assess screw placement by cone beam computed tomography (CBCT) and gross examination by two evaluators. Results: The total procedure time was 25–62 min (median 33.5). During the procedure, 11–21 radiographs (median 18.5) were taken. The postoperative gross examination revealed an excellent screw placement in nine NB and poor in one. This could not be reliably assessed with post-procedure CBCT. Conclusion: The described technique achieves an excellent screw placement in 9/10 bones without disrupting the articular or flexural surface of the NB and with no protrusion of the screw head or tip, in a median procedure time of under 35 min. Clinical significance: Adequate screw placement is paramount for NB fracture repair. The described approach under radiographic guidance allows adequate screw placement using the ACD to stabilize the NB by lateral to medial compression. This technique facilitates adequate screw placement within the NB without the use of advanced imaging techniques.
Keywords: ddc:630